2016
DOI: 10.1177/2167696816631845
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Financial Identity Development in Emerging Adulthood

Abstract: To explore how emerging adults grapple with the increasing demands of fiscal responsibility, the present study tests a model of identity formation in the domain of finance. We draw on Erikson's (1950, 1968) theory of identity formation as operationalized by Marcia's (1966) identity status model, which details four identity statuses: achieved, foreclosed, moratorium, and diffused. A sample of college students (N = 1,511) were surveyed at two time points: In their first (ages 18-21, T1) and fourth (ages 21-24, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Notably, composite reliability for the foreclosed status was questionable to some extent, as it did not reach the recommended minimum levels of .70. However, it was considered sufficient for the exploratory research purpose of this study (Hair et al, 2009) and was very similar to that found in previous similar studies (e.g., Bosch et al, 2016).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, composite reliability for the foreclosed status was questionable to some extent, as it did not reach the recommended minimum levels of .70. However, it was considered sufficient for the exploratory research purpose of this study (Hair et al, 2009) and was very similar to that found in previous similar studies (e.g., Bosch et al, 2016).…”
Section: Methodssupporting
confidence: 83%
“…In addition, the mediator role of the proximal outcomes was in most cases only assumed rather than empirically investigated (Gudmunson & Danes, 2011). More so, in recent years, researchers recognized that identity formation in the domain of personal finances, which is not addressed in FFS model (Gudmunson & Danes, 2011), is also an important part of financial capabilities and a potential mediator between parental financial socialization and emerging adults’ financial behaviors (Bosch, Serido, Card, Shim, & Barber, 2016; Shim, Serido, Bosch, & Tang, 2013; Sorgente, Lanz, Serido, & Shim, 2018).…”
Section: Financial Identitymentioning
confidence: 99%
“…Regarding theoretical implications, these findings highlight that succeeding in salient developmental tasks of emerging adulthood plays a role in promoting or hindering some financial capabilities in this period. Although recent studies have investigated predictors of financial identity and its effects on financial behaviors (Bosch et al, 2016;Shim et al, 2013), this study extends these findings by offering additional insights on the interplay between general identity formation processes, self-regulatory identity functions, and capacities for spending self-control.…”
Section: Discussionmentioning
confidence: 65%
“…More recently, scholars recognized that succeeding in salient developmental tasks might also contribute to the formation of these capabilities. Specifically, one task that is likely to play an important role in emerging adulthood is the development of identity (e.g., Bosch, Serido, Card, Shim, & Barber, 2016; Claes, Luyckx, Vogel, Verschueren, & Müller, 2018; Claes, Müller, & Luyckx, 2016; Shim, Serido, Bosch, & Tang, 2013).…”
Section: Formation Of Personal Identity and Financial Capabilitiesmentioning
confidence: 99%
“…Financial stability and independence in emerging adulthood influences numerous facets of well-being such as education and career trajectory (Terriquez & Gurantz, 2015) and identity formation (Bosch et al, 2016). However, emerging adults are struggling to find this stability and independence (Seiffge-Krenke, 2013), and they feel only “moderately prepared” for financial adulthood (Clarke et al, 2005).…”
mentioning
confidence: 99%